Executive Remuneration: Robustness of Stock Based Compensation in FTSE 100 Companies c - Pugla, Mohit (2006)
Executive compensation is a hotly debated topic among academics and practitioners and attracts widespread attention. This paper provides an overview of the main theoretical concepts relating to executive compensation with its main focus on the recent innovations in executive remuneration in the UK namely, executive share options and long-term incentive plans. This paper is grounded in the agency theory and uses a sample of thirty companies from the FTSE 100 index to examine the robustness of these innovations in executive remuneration in bridging the already existing gap between the interests of the shareholders and executives. I first consider the relationship between the PPS of the CEOs and firm size. My results are consistent with prior evidence and show that there is a strong negative relationship between the PPS of the CEO and firm size. Secondly, I explore whether company performance is influenced by the incentives of the board. My results indicate that no relationship could be established between firm performance and incentives. Finally, unlike much prior work, I include non-CEO executives in the analysis to examine whether PPS increases through organizational levels. My results are inconsistent with the tournament theory and show that with increase in organizational levels pay-performance sensitivity does not increase.